SA Heart® Statement on COVID-19 and cardiovascular disease - Jankelow, David; Manga, Pravin; Ntsekhe, Mpiko; Khan, Sajidah; Cupido, Blanche; Ntsinjana, Hopewell; Zühlke, Liesl; Smit, Francis (SA Heart Journal, 2020)
The South African Heart Association (SA HeartR) is an association of cardiologists, paediatric cardiologists, cardiac surgeons, as well as allied cardiac professionals, whose vision is to advance cardiovascular care for each of our country’s citizens and to be the scientific leaders in South African cardiac healthcare delivery, education and research. As such, we are ideally placed to advise the National Department of Health (NDoH) about the cardiac implications of the COVID-19 pandemic, as well as how we tackle non-communicable cardiovascular disease (NCD) going forward.